Antioxidants as recipes for efavirenz-induced liver damage: A study in albino rats - Adikwu, Elias; Bokolo, Bonsome (Journal of Contemporary Medical Sciences, 2018)
Objective: Hepatotoxicity is a clinical challenge associated with the use of efavirenz (EFV). This study investigated the effects of n-acetylcysteine (NAC), vitamins C and E on EFV-induced hepatotoxicity in albino rats. Methods: Rats were divided into groups and administered with NAC (20mg/kg), Vit C (50mg/kg), Vit E (50mg/kg), Vit C+ E and 60mg/kg of EFV respectively. Rats were also divided into groups and pretreated with NAC, Vit C, E, and combined doses of Vit C+E prior to treatment with EFV for 15 days respectively. After drug administration rats were sacrificed and serum was collected and evaluated for liver function parameters. Rats were dissected, liver was collected weighed and evaluated for alkaline phosphatase (ALP), alanine aminotransferase (AST), aspartate aminotransferase (ALT), gamma glutamyl transferase (GGT), lactate dehydrogenase (LDH), malondialdehyde (MDA), super oxide dismutase (SOD), catalase (CAT), glutathione (GSH), gluthatione peroxidase (GPX) levels and pathological damage. Results: Effects were not significant (p>0.05) on body and liver weights, however, the levels of AST, ALT, AST, GGT, LDH, CB, TB and MDA were increased significantly (p<0.05) whereas SOD, CAT, SOD, GSH and GPX were decreased significantly (p<0.05) in EFV-treated rats in comparison to control. The liver of EFV-treated rats showed necrosis of hepatocytes. Nevertheless, EFV-induced alterations in the above parameters were significantly (p<0.05) ameliorated in antioxidants pretreated rats. The combined doses of Vit C and E produced the best and significant (p<0.05) ameliorative effects in comparison to their individual doses. Conclusion: This study shows the prospects of antioxidants as candidates for the treatments of efavirenz-induced hepatotoxicity.